Use of Self-Complementary Adeno-Associated Virus Serotype 2 as a Tracer for Labeling Axons: Implications for Axon Regeneration - Liu, Yingpeng; Keefe, Kathy; Tang, Xiaoqing; Lin, Shen; Smith, George M. (PloS one, 2014)
Various types of tracers are available for use in axon regeneration, but they require an extra operational tracer injection, time-consuming immunohistochemical analysis and cause non-specific labeling. Considerable efforts over the past years have explored other methodologies, especially the use of viral vectors, to investigate axon regeneration after injury. Recent studies have demonstrated that self-complementary Adeno-Associated Virus (scAAV) induced a high transduction efficiency and faster expression of transgenes. Here, we describe for the first time the use of scAAV2-GFP to label long-projection axons in the corticospinal tract (CST), rubrospinal tract (RST) and the central axons of dorsal root ganglion (DRG) in the normal and lesioned animal models. We found that scAAV2-GFP could efficiently transduce neurons in the sensorimotor cortex, red nucleus and DRG. Strong GFP expression could be transported anterogradely along the axon to label the numerous axon fibers from CST, RST and central axons of DRG separately. Comparison of the scAAV2 vector with single-stranded (ss) AAV2 vector in co-labeled sections showed that the scAAV2 vector induced a faster and stronger transgene expression than the ssAAV2 vector in DRG neurons and their axons. In both spinal cord lesion and dorsal root crush injury models, scAAV-GFP could efficiently label the lesioned and regenerated axons around the lesion cavity and the dorsal root entry zone (DREZ) respectively. Further, scAAV2-GFP vector could be combined with traditional tracer to specifically label sensory and motor axons after spinal cord lesion. Thus, we show that using scAAV2-GFP as a tracer is a more effective and efficient way to study axon regeneration following injury.